The Types of Grammatical Errors on Instagram Captions Written by K-Popers - Hanifatus, Retni; Faiza, Dinar; Rosyidah, Naeli (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2022)
This research aimed to analyze the types of grammatical errors on Instagram captions written by K-Popers. The existence of social media has become a common communication among K-Popers national and international boundaries. Instagram is one of the social media platforms which has received a lot of attention from K-Popers. K-Popers usually upload their idols’ photos or videos on Instagram, and they usually use English as their caption to make it is easy to understand by K-Popers around the world. Through the English captions on Instagram, grammatical errors often occur in their English. This research used descriptive qualitative method. The researcher chose the accounts from hashtag #kpopshoutout. The researcher had figured out the data which were posted on January to April 2021 from six K-Popers which have been chosen in the form of sentences on Instagram captions. Five K-Popers in different accounts which have been chosen by the researcher, they were: @jsoo.yaaa_, @do.exokyung, @bts.bighotofficial, @bts.bighitotfical, and @nutshell.skz.The researcher analyzed 50 captions from six K-Popers accounts. Based on the analysis result by using Dulay’s theory, there are four types of grammatical errors based on Surface Strategy Taxonomy, they are omission, addition, mis-formation, and mis-ordering. Based on the analysis, it can be concluded that omission was the most type of grammatical error and addition was the least type of grammatical errors that the researcher found in this research.